Effects of functional training on skill performance and movement quality among skilled youth male tennis players: A cluster randomized control trial - Xiao, W.; Bu, T.; Zhao, F.; Zhang, J.; Bai, X.; Geok, S. K. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Purpose Functional training to improve athletes` technical performance and movement quality is becoming increasingly popular, but few studies have focused on young tennis players. The aims of this study were to compare the effects of 12 weeks of functional training on skilled youth male tennis players` skill performance and movement quality.